ChemInform Abstract: Generation of the Methoxycarbonyl Radical by Visible‐Light Photoredox Catalysis and Its Conjugate Addition with Electron‐Deficient Olefins. Issue 42 (September 2016) - Slutskyy, Yuriy; Overman, Larry E.
Abstract: for the direct and regioselective construction of a 1, 4‐dicarbonyl structural motif